PROOF OF SURPLUS ACCRUING TO A HOLDING COMPANY WHEN THE INVESTMENT IN A SUBSIDIARY IS CARRIED AT COST. - Karrenbrock, W. K. (The Accounting Review, 1958)
The proof of surplus accruing to the parent company as presented in the article deals with two types of problems: the parent company owns a controlling interest in a subsidiary company for a portion of a year and the subsidiary owns no stock of the parent, and the parent company owns a controlling interest in a subsidiary company for a portion of a year and the subsidiary company owns a portion of the stock of the parent company for a greater portion of the same year. When the cost method of carrying the investment account is used, the investment account remains unaffected by profits, losses, and dividends of the subsidiary. While increases and decreases in subsidiary net worth as a result of profits and losses are disregarded on the books of the parent, the declaration of a dividend by a subsidiary is recorded on the books of the parent company by a debit to dividends receivable and a credit to dividend income or earned surplus. Receipt of the dividend from the subsidiary results in a debit to cash and a credit to dividends receivable.